Teaching equations and inequalities in high school algebra using two strategies an experimental study - Agbisit, Clarita F.
This is concerned with the determination of relative merits of the discovery strategy in teaching certain concepts and principles in high school algebra. The primary purpose of this study was to establish the benefits derived from the advocated discovery approach to the teaching of mathematics.